Hepatoprotective And Pharmacology Studies Of Standardized Ethanolic Extract Of Curcuma Xanthorrhiza Roxb - Devaraj, Sutha (2012)
The hepatoprotective and pharmacology properties of C. xanthorrhiza rhizome extracts were investigated using in vivo and in vitro model assays. Prior to the bioassays, C. xanthorrhiza rhizome ethanolic extract (CXRE) were subjected to liquid-liquid extraction resulting in hexane, ethyl acetate and water fractions. Xanthorrhizol was employed as the marker to standardize the CXRE and fractions respectively. The presence of terpenoids, flavonoids, cardiac glycosides and saponin were observed in the standardized CXRE through qualitative phytochemical screening analysis. The acute oral toxicity of standardized CXRE showed an LD50 of greater than 5,000 mg/kg, indicating CXRE is relatively safe for preclinical investigation in animals. Further, the standardized CXRE and its fractions (hexane, ethyl acetate and water) were tested for antioxidant activity. In FRAP, DPPH and ABTS assay, the highest antioxidant activity was found in hexane fraction compared to the CXRE, ethyl acetate fraction and water fractions in line with their total phenolics and flavonoids content. The total phenolics and flavonoids content of hexane fraction were 61.00 mg GAE/g and 92.80 mg CAE/g respectively. The standardized C. xanthorrhiza rhizome hexane fraction (CXRH) at doses 125, 250 and 500 mg/kg was further tested for hepatoprotective activity against CCl4- induced hepatic damage in rats.